Financing long-term care: Replacing a welfare model with an insurance model - Walter M. Cadette (Levy Economics Institute of Bard College, 2000)
The nation is not prepared to deal with the jump in expenditures for long-term care that will come with the aging of the baby-boom generation. Only a small part of that care is paid for privately (out-of-pocket or through private insurance). Most is financed through Medicaid, the program that is intended to ensure medical care for the indigent. This use of Medicaid comes at a high cost for individuals and society: the allotment of more than a third of the Medicaid budget to long-term care; a two-tier care system; and the commandeering of limited funds by middle- and high-income people through elaborate estate planning to circumvent eligibility requirements. These problems would be mitigated by replacing the welfare model with an insurance model - voluntary or compulsory private insurance, with subsidies through income-scaled tax credits to ensure affordability. An equitable and efficient system could be created with a blend of public money, private insurance, and other private saving, with a safety net for those in greatest need.
Keywords: 330